2003
DOI: 10.1177/004051750307301212
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Surface Oxidized Wool

Abstract: A wool surface is oxidized with potassium permanganate in saturated salt solutions. The surface patterns, breaking strength, friction coefficient, and electrical resistance of oxidized and un-oxidized wool are then examined, and the static electricity in two resulting fabrics is investigated. Changes in the wool surface have a significant effect on its physical properties.A number of studies have considered chemical modifications [1][2][3]8] of the wool surface and their effects on felting shrinkage, and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Martel et al observed that usage of sodium hypophosphite (SHP) can catalyze the reaction between citric acid and wool (18). KMnO 4 consumed by the wool increases with time, temperature and concentration of treating bath (19,20). The treatment produced some bleaching effects on the wool (19,20).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Martel et al observed that usage of sodium hypophosphite (SHP) can catalyze the reaction between citric acid and wool (18). KMnO 4 consumed by the wool increases with time, temperature and concentration of treating bath (19,20). The treatment produced some bleaching effects on the wool (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…KMnO 4 consumed by the wool increases with time, temperature and concentration of treating bath (19,20). The treatment produced some bleaching effects on the wool (19,20). Acid cross‐linking agents used for durable press finishing have been actively investigated in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been carried out to better understand the impacts of diverse surface modification methods on wool shrinkage. 36 McPhee has reported that reducing the oxidized samples by sodium bisulfite has two distinct effects: first, precipitated MnO 2 is removed from the wool, and second, the reduction of the oxidized wool causes an increased shrink resistance. In addition, it has been demonstrated that through the oxidation process, the sharp edges of wool scales are fully removed.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been demonstrated that through the oxidation process, the sharp edges of wool scales are fully removed. 36 Kantouch et al 16 illustrated that the oxidation process in an acidic solution gave better antishrink properties in comparison with those of in alkali solutions. Also, they declared that the amino acids cystine, tyrosine, and tryptophan were greatly affected by the KMnO 4 treatment.…”
Section: Resultsmentioning
confidence: 99%